Frequency of dairy products in preschool centers’ meals with - Irena Colić Barić; Mirjana Brlečić (Mljekarstvo)
It is well known that dairy products contain a great number of essential nutrients having positive influence on human health. The aim of this study wasmto determine the nutritive value of meals and frequency of dairy products in preschool centers’ meals with regard to season. For assessment of energy and nutritive value as well ascertain food frequency in daily diet during four seasons the monthly reports menu were used. According to the results the energy gained by the meals was adequate. Proteins were present in high amount (154.3 % RDA). The energy fraction of dairy products in average was 14.3 % what is for children age 4-6 less than recommended. Those products were served in average 6.5 times/5 days what represented 1.6 serving units per day. Milk was present in daily meals on regular basis, yogurt was present twice and cheese ones a week or even less. Milk and dairy products ensured of 362 mg (45.5 % DRI) of calcium, 272 mg (354.4 % DRI) of phosphorus, 36.3 mg (27.9 % DRI) of magnesium and 0.5 mg (83.3 % DRI) of vitamin B2. Thus, dairy products should be included at least twice in daily preschool meals. According to season significant difference was detected, mostly between spring and summer, with regard to milk and dairy products. With regard to energy and nutritive value difference between spring and autumn have been established.